2000
DOI: 10.2224/sbp.2000.28.5.471
|View full text |Cite
|
Sign up to set email alerts
|

Later Adolescents' Reactions to Three Types of Childhood Teasing: Relations With Self-Esteem and Body Image

Abstract: The purposes of this study were: 1) to examine how predictive three types of childhood teasing (competency, weight, and appearance) were of later self-esteem; and 2) to examine how predictive these same three variables were of later body image. Additionally, the pattern of relations for each gender was be explored. Each of these questions will be explored for males and females separately. The participants in this study were 89 female and 75 male undergraduates from two midwestern universities, with a mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 16 publications
4
36
0
Order By: Relevance
“…Previous studies indicated a relationship between weight preoccupation and self esteem (e.g., Abell & Richards, 1996;Gleason et al, 2000;Lowery et al, 2005;Milligan & Pritchard, 2006;Shea & Pritchard, 2007), as well as between weight preoccupation and gender (e.g., Erol et al, 2006;Johnson et al, 2004;Macedo et al, 2007;Milligan & Pritchard, 2006;Pritchard, 2008a;Shea & Pritchard, 2007). These findings were replicated in the present study.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Previous studies indicated a relationship between weight preoccupation and self esteem (e.g., Abell & Richards, 1996;Gleason et al, 2000;Lowery et al, 2005;Milligan & Pritchard, 2006;Shea & Pritchard, 2007), as well as between weight preoccupation and gender (e.g., Erol et al, 2006;Johnson et al, 2004;Macedo et al, 2007;Milligan & Pritchard, 2006;Pritchard, 2008a;Shea & Pritchard, 2007). These findings were replicated in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…Low self-esteem has been found to relate to several types of weight preoccupation behaviors including drive for thinness (Milligan & Pritchard, 2006;Shea & Pritchard, 2007), poor body image and body dissatisfaction (Abell & Richards, 1996;Gleason, Alexander, & Somers, 2000;Lowery et al, 2005;Milligan & Pritchard, 2006;Shea & Pritchard, 2007), bulimic symptoms (Gilbert & Meyer, 2005; Mora-Giral, Raich-Escursell, Segues, Torras-Claraso, editing, corrections, structural formatting and other quality control mechanisms, may not be reflected in this document. Changes may have been made to this work since it was submitted for publication.…”
Section: Self Esteem and Weight Preoccupationmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty to 110 is mild concern, 111 to 140 is moderate concern, and over 140 is severe concern with shape. The BSQ has high internal consistency and reliability at .97 and .88, respectively (Rosen, Jones, Ramirez, & Waxman, 1996) and has been used in the adolescent population (Gleason, Alexander, & Somers, 2000;Rodríguez-Cano, Beato-Fernández, & Llario, 2006).…”
Section: Body Dissatisfactionmentioning
confidence: 99%
“…Certain contexts can elicit feelings of body anxiety or shame for women, given how closely physical appearance is linked to self-esteem (1). To manage these threatening situations, coping strategies are often implemented, as individuals engage in cognitive, emotional or behavioural adjustments in order to lessen the stress associated with an uncomfortable situation (2).…”
Section: Introductionmentioning
confidence: 99%